Optimization of Local Basil, Kandangu Mbuku Type as a Natural Preservative for Chicken Eggs - Ndapa Behar, Jordi; Tamu Ina, Yessy; Umbu Hina Pari, Aris (Bulletin of Applied Animal Research, 2024)
The aim of this research is to determine the effect of different concentrations of kandangu Mbuku flour on water content, antioxidants, Ph, and organoleptics in salted eggs from purebred chickens, including (color, taste, texture and preferences). The research was carried out in the integrated laboratory at Wira Discourse Christian University, Sumba. This research used 200 purebred chicken eggs. This research used a completely randomized design (CRD) consisting of 4 treatments and 5 replications, namely P1= 20% concentration of kandangu mbuku flour, P2= 25% concentration of kanu mbuku flour, P3= 30% concentration of kandangu mbuku flour, P4= concentration 35% corn flour. So there are 20 sample units. The variables observed were water content, pH, antioxidants, and organoleptics (color, taste, texture and preferences). The data obtained is analyzed with a confidence level of 5%, if the results have a real effect then it will be continued with a real difference test. Treatment of kandangu Mbuku flour with each different level can have an influence on changes in color, taste, texture and preferences. However, the highest concentration, namely 35%, can increase the percentage of water content in the egg white and yolk, as well as increase the pH of the egg. The higher the concentration of kadangu mbuku flour given, the more intense the color of the egg yolk will be. Keywords: Cage, Salted Egg, Antioxidant, Organoleptic